PRODaUKSI PUPUK KOMPOS HASIL FERMENTASI LIMBAH TERNAK AYAM PLUS & APLIKASINYA PADA TANAMAN BAWANG DAUN (Allium fistulosum) - Pendana, Sufriono; Limbongan, Yusuf La'lang; Galla', Ernytha Anytha (Institute of Computer Science (IOCS), 2025)
This study aims to evaluate the results of chicken manure compost fermentation mixed with rice washing water and rice husk waste and to test its effect on the growth of leek plants (Allium fistulosum L.). The study was conducted from June to November 2024 at the Experimental Park of the Faculty of Agriculture, Toraja Christian University of Indonesia, Tarunlip Matalo District, North Toraja Regency, South Sulawesi. The method used was a randomized block design (RAK) with five compost dose treatments, namely K0 (no treatment), K1 (50 g/plastic bag), K2 (100 g/plastic bag), K3 (150 g/plastic bag) and K4 (200 g/plastic bag). The results showed that the provision of chicken manure compost had a significant effect on all observed parameters. A dose of 150 g/polybag (K3) produced optimal growth in terms of plant height, number of leaves, stem diameter and wet weight of plants. This proves that fermented chicken manure waste compost with additional materials such as rice water and rice husk waste can be an effective alternative organic fertilizer to increase the productivity of spring onions sustainably.